2022
DOI: 10.3390/jcm11030712
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Oximetry-Monitored Nitroglycerin Infusion and Tissue Perfusion during Rewarming of Cardiopulmonary Bypass in Cardiac Surgery: A Prospective Randomized Trial

Abstract: Background: Nitroglycerin facilitates microcirculation and oxygen delivery through vasodilation. The purpose of this study was to clarify the effects of nitroglycerin-induced vasodilation and potential hypotension on tissue perfusion under cerebral oximetry monitoring during rewarming in cardiopulmonary bypass. Methods: Elective cardiac surgical patients were randomly assigned to either a nitroglycerin group (n = 32) with an intravenous infusion of 1–5 mcg/kg/min or a control group (n = 31) with 0–0.1 mcg/kg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In 2010, a clinical study by Boerma et al [68] found that nitroglycerin could not significantly improve sublingual microvascular perfusion and prognosis in septic patients. Similarly, Chen et al [69] found that intravenous nitroglycerin (1-5 mcg/kg/min) did not improve microcirculatory perfusion in patients with hypothermic cardiopulmonary bypass during rewarming. However, in the same year, Greenwood et al [70] found that local application of nitroglycerin could improve microcirculatory perfusion in patients after cardiac surgery.…”
Section: Microcirculation-guided Treatmentsmentioning
confidence: 94%
“…In 2010, a clinical study by Boerma et al [68] found that nitroglycerin could not significantly improve sublingual microvascular perfusion and prognosis in septic patients. Similarly, Chen et al [69] found that intravenous nitroglycerin (1-5 mcg/kg/min) did not improve microcirculatory perfusion in patients with hypothermic cardiopulmonary bypass during rewarming. However, in the same year, Greenwood et al [70] found that local application of nitroglycerin could improve microcirculatory perfusion in patients after cardiac surgery.…”
Section: Microcirculation-guided Treatmentsmentioning
confidence: 94%